2005
DOI: 10.1002/polb.20640
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal surface‐grafted polymer gradients: A versatile combinatorial platform

Abstract: Orthogonal polymer brush gradients are assemblies of surfaceanchored macromolecules, in which two material properties of the grafted chains (e.g., grafting density, molecular weight) vary independently in orthogonal directions. Here, we describe the formation and applications of two such orthogonal assemblies, involving: (1) molecular weight and grafting density (MW/r) gradients of a given polymer and (2) molecular weight gradients (MW1/MW2), of two different polymers. Each point on orthogonal gradient substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 62 publications
1
59
0
Order By: Relevance
“…The density of polymers grown from a surface has been tuned rationally by controlling the initial initiator concentration on the substrate [25,[35][36][37][38][39][40][41]. In a variation of this process, Jones et al [34] reported controlling the polymer density of ATRP-synthesized brushes by varying the concentration of the initiator molecules in self-assembled monolayers.…”
Section: Effect Of Pqa Chain Density On Efficacy Of E Coli Killmentioning
confidence: 98%
“…The density of polymers grown from a surface has been tuned rationally by controlling the initial initiator concentration on the substrate [25,[35][36][37][38][39][40][41]. In a variation of this process, Jones et al [34] reported controlling the polymer density of ATRP-synthesized brushes by varying the concentration of the initiator molecules in self-assembled monolayers.…”
Section: Effect Of Pqa Chain Density On Efficacy Of E Coli Killmentioning
confidence: 98%
“…In addition, a key feature of grafted statistical copolymers is that they present stable and intimate blends of disparate chemical species. Since the different monomers are bound within the same chains, the system will not undergo lateral clustering typical of mixed homopolymer brushes [61], or segment segregation seen in block copolymer brushes [45,58], both of which can cause spatial chemical heterogeneities on the scale of 10 nm or more. Accordingly, if local surface-chemical homogeneity is needed from a surface chemistry gradient library, statistical copolymer gradients present an advantage.…”
Section: Gradient Polymer Brush Librariesmentioning
confidence: 98%
“…In order to create more robust and diverse surface chemistry gradients, NIST researchers turned to surface-initiated polymerization (SIP) techniques [43,44] to create libraries of grafted polymer "brushes" that would systematically change in their molecular composition and architecture. In this endeavor, the pioneering work of Genzer and coworkers [45][46][47][48] provided examples to build upon, including the creation of gradient libraries of polymer brush length and grafting density.…”
Section: Gradient Polymer Brush Librariesmentioning
confidence: 99%
“…[74][75][76][77][78] Several researchers have made surface-grafted polymers that have gradients in variables such as polymer chain length, composition, and graft density. [79][80][81][82][83][84][85][86][87][88][89] …”
Section: Formation Of Gradient Librariesmentioning
confidence: 99%